Immigrants as Symbolic Assailants: Crimmigration and Its Discontents - Jiang, Jize (International criminal justice review, 2018)
Despite little evidence of an immigration-crime nexus, many American jurisdictions have adopted a punitive approach to undocumented immigrants and an increasingly restrictive and exclusive system of immigration control. The extensive deployment of criminal justice measures to address the immigration “problem” led to the growth of a crimmigration apparatus—a mesh of immigration and criminal justice systems. Drawing on extant literature and applying the framework of the penal field, the article examines the social dynamics, processes, and consequences of crimmigration. It is argued that the portrayal of immigrants as “symbolic assailants” has facilitated the creation and operation of crimmigration under the guise of crime prevention rather than for addressing terrorism and national security—the presumed purpose of utilizing crimmigration practices. The current configuration of crimmigration across the United States is the interactive product of minority threat, partisan politics, and federalism of the American government system, which have jointly formed a “multilayered patchwork” of immigration control. The article first outlines the analytical framework; reviews the social construction of immigrant “criminality”; and describes the punitive and exclusive laws, policies, and enforcement practices established as responses to this “threat.” The dilemmas, contradictions, and contestations associated with crimmigration, including collateral impacts on immigrants, their families and communities, and the criminal justice system, are analyzed; and policy implications are drawn and discussed.